Sarcopenia Is Associated With Increased Risk of Abnormal Sleep Duration in the Older People: A 10‐Year Cohort Study From China - Yimi Wang; Weixin Chen; Chun Wang; Lingzhi Li; Bingqing Bi; Shugang Li; Hao Wu (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background With the acceleration of the aging process, health issues of older people have gradually become one of the most important research topics. The older people experience significant reductions in muscle mass and physical performance. Cross‐sectional studies have found an association between the sarcopenia and sleep duration. Due to lack of evidence of longitude study, it is necessary to investigate the association between sarcopenia and sleep duration in the older people. Methods This study utilized longitudinal data including 2061 older people from China Health and Retirement Longitudinal Study 2011–2020. Diagnosis was made based on the Asian Working Group for Sarcopenia criteria 2019. There were 246 participants with sarcopenia, 628 participants with possible sarcopenia and 1187 participants with nonsarcopenia. Kaplan–Meier curve, log‐rank test and Cox proportional risk model were used to explore the relationship between sarcopenia exposure and clinical outcome of abnormal sleep duration. Three models adjusting for different factors were built, and hazard ratios (HRs) were calculated. Restricted cubic spline analyses explored the exposure–response relationship between sarcopenia components and abnormal sleep duration incidence, while receiver operating characteristic curve was used to assess their predictive power. Results The incidences of short or long, decreased sleep duration of the sarcopenia and possible sarcopenia groups in the overall population were significantly higher than those of the nonsarcopenia group (respectively, p < 0.001). Sarcopenia (HR = 1.240, 95% CI [confidence interval]: 1.023–1.417) was significantly associated with an increased risk of abnormal sleep duration by Cox model analysis with adjusting factors. Results of analyses stratified by sleep duration showed that sarcopenia (HR = 1.566, 95% CI: 1.192–2.057) and possible sarcopenia (HR = 1.286, 95% CI: 1.054–1.570) were positively associated with long sleep duration. Higher ASM (χ2 = 94.02, p < 0.001) and handgrip strength (χ2 = 94.55, p < 0.001), as well as lower five‐time chair stand test (χ2 = 81.33, p < 0.001) showed an exposure‐response relationship with sleep duration. The proportion of the condition of change in sleep duration from normal to < 6 h or > 8 h in the sarcopenia and possible sarcopenia groups was significantly different from the nonsarcopenia group (p < 0.05). Conclusions Our results suggest that sarcopenia and possible sarcopenia are associated with abnormal sleep duration and the decrease of ASM and handgrip strength, and the increase of the five‐time chair stand test is positively related to abnormal sleep duration, which implies that delaying the development of sarcopenia could be a new pathway to improve sleep health in older people.